2018
DOI: 10.1590/1678-5150-pvb-5689
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of serum lactate levels, blood glucose values and blood gas values in sheep, newborn lambs and placenta

Abstract: RESUMO.-[Avaliação da concentração de lactato sérico, glicemia e hemogasometria de ovelhas, cordeiros recém-nascidos e placenta.] Os principais desafios da transição fetal-neonatal são a estabilização do equilíbrio ácido-básico, glicemia e oxigenação ao longo das primeiras 24 horas de vida. Falhas nesse sistema são a maior causa de morte nesse período e os estudos de viabilidade neonatal tem se concentrado nas avaliações destas variáveis. O objetivo do presente estudo foi avaliar a comparação da lactatemia mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 20 publications
1
1
0
Order By: Relevance
“…In this trial, the glycaemia values recorded in the lambs within 1 h of parturition agreed with those reported by Vannucchi et al (2012), who considered concentrations of 46.86±21.87 mg/dL as physiological. Furthermore, the glycaemia concentrations recorded in the lambs of the four experimental groups from 24 to 72 h after birth coincided with those reported by Silva et al (2018), who suggested that the elevation of glucose was the result of the contribution of this metabolite through colostrum suckling.…”
Section: Discussionsupporting
confidence: 87%
“…In this trial, the glycaemia values recorded in the lambs within 1 h of parturition agreed with those reported by Vannucchi et al (2012), who considered concentrations of 46.86±21.87 mg/dL as physiological. Furthermore, the glycaemia concentrations recorded in the lambs of the four experimental groups from 24 to 72 h after birth coincided with those reported by Silva et al (2018), who suggested that the elevation of glucose was the result of the contribution of this metabolite through colostrum suckling.…”
Section: Discussionsupporting
confidence: 87%
“…Monitoring the inflammatory response is a challenge because the signs of inflammation are not always clear [27]. Hemogasometry is an important technique for assessing acid-base balance in various diseases, capable of clarifying severity and predicting clinical evolution [15,26,28]. However, in the acute phase of disease, it may not detect changes suggestive of inflammatory process [1].…”
Section: Introductionmentioning
confidence: 99%